Women's Movements and Constitution Making after Civil Unrest and Conflict in Africa: The Cases of Kenya and Somalia. Issue 1 (23rd March 2016) - Tripp, Aili Mari
Abstract : As numerous conflicts have come to an end in Africa over the past two decades, women's movements have sought to advance a women's rights agenda through peace accords; through constitutional, legislative, and electoral reforms; as well as through the introduction of gender quotas. This article focuses the impact women's movements have had in shaping constitutions after periods of turmoil, particularly in areas of equality, customary law, antidiscrimination, violence against women, quotas, and citizenship rights. It demonstrates how countries that have come out of major civil conflict and violent upheaval in Africa after the mid-1990s—but especially after 2000—have made more constitutional changes with respect to women's rights than other African countries. The second part of the article provides two examples of how women's movements influenced constitutional changes pertaining to gender equality as well as the difficulties they encountered, particularly with respect to the international community.